2014
DOI: 10.1093/jxb/eru424
|View full text |Cite
|
Sign up to set email alerts
|

Transcripts of two ent-copalyl diphosphate synthase genes differentially localize in rice plants according to their distinct biological roles

Abstract: HighlightExpression of the diterpene synthase gene for gibberellin biosynthesis occurs in tissues different from those in which its isoform for phytoalexin biosynthesis is expressed, reflecting their distinct biological roles in rice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Nevertheless, Os-CPS2 is important for plant defense, as evidenced by the increased susceptibility of the Os-cps2 lines to both Xoo and M. oryzae. This disparity may reflect the differential expression patterns of the two ent-CPP producing CPSs, as Os-CPS1 is selectively expressed in the vascular bundle, while Os-CPS2 is largely expressed in epidermal cells (Toyomasu et al, 2015). Thus, in the absence (or upon suppression) of Os-CPS2 expression, ent-CPP-derived phytoalexins may not be produced in the epidermal tissue, allowing establishment of pathogen infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Os-CPS2 is important for plant defense, as evidenced by the increased susceptibility of the Os-cps2 lines to both Xoo and M. oryzae. This disparity may reflect the differential expression patterns of the two ent-CPP producing CPSs, as Os-CPS1 is selectively expressed in the vascular bundle, while Os-CPS2 is largely expressed in epidermal cells (Toyomasu et al, 2015). Thus, in the absence (or upon suppression) of Os-CPS2 expression, ent-CPP-derived phytoalexins may not be produced in the epidermal tissue, allowing establishment of pathogen infection.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there may be a distinct pool of GGPP that is tapped for more specialized diterpenoid metabolism in rice plant leaves, which seems to be separate from that utilized for gibberellin biosynthesis or in the production of photosynthetic pigments (this latter presumably reflects the predominant metabolic fate for GGPP overall). These distinct pools also may reflect the separation of these various metabolic processes into distinct tissues, as Os-CPS1 is selectively expressed in the vascular bundle where gibberellin metabolism occurs, while Os-CPS2, and presumably Os-CPS4, are largely expressed in epidermal cells (Toyomasu et al, 2015). These tissues are further separate from the mesophyll where photosynthesis is localized.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, TPSs on S. italica chromosome 7 have syntenic orthologs mapping to one chromosome in S. viridis (chromosome 6), S. bicolor (chromosome 6) and Z. mays (chromosome 2), but different chromosomes in P. hallii (chromosomes 2 and 7), B. distachyon (chromosomes 3 and 5) and O. sativa (chromosomes 3, 4 and 8), indicating diverse chromosomal origins for evolutionary hotspots for TPS genes across the Poaceae (Table S3). Interestingly, SiTPS34 (chromosome 9) with a predicted ent-CPP synthase function, was placed in a syntenic network with known ent-CPP synthases from rice (OsCPS1, chromosome 2), maize (ZmAN1, chromosome 1) and switchgrass (PvCPS14/15, chromosome 9) (Bensen et al, 1995;Toyomasu et al, 2015;Pelot et al, 2018). Similarly, the predicted ent-kaurene synthases SiTPS28/29 (chromosome 7) clustered in a syntenic network with ent-kaurene synthases from rice (OsKS1, chromosome 4), maize (ZmKSL3/5, chromosome 2) and switchgrass (PvKSL13/15, chromosome 7).…”
Section: Identification Of Tps Candidatesmentioning
confidence: 99%
“…When the full length CDS of OsKO1 and OsKO2 genes were fused with GFP respectively, no GFP signal could be detected in both constructs, although there was strong signal in the cell for the empty pGFP2 vector control (S4 Fig). Previous study has shown that transit peptides at the N-termini for OsCPS1 and OsCPS2 are enough for their transport into plastid [35], we then used the Nterminal 150 amino acids of OsKO1 and N-terminal 140 of OsKO2 proteins containing transit peptides to fuse with GFP, respectively. The signal of OsKO1 could be detected at both plastid and other membrane system, whereas, OsKO2 signal could be only detected at plastid membrane (Fig 5A).…”
Section: Subcellular Localization and Expressional Pattern Of Osko1mentioning
confidence: 99%